Nutrient Status, Diet Quality and Growth Parameters of Children with Autism Spectrum Disorder in Northern Cyprus - Zeybek, Sabiha Gökçen; Yurttagül, Mine (Progress in Nutrition, 2020)
Background: There is no literature on the nutritional status and growth parameters of autistic children in Northern Cyprus. This study is the first to provide information about them. The aim of this study is to determine the nutritional status, anthropometric measurements, and healthy eating indices of autistic children who are studying at private educational centers in Northern Cyprus. Method: All children with Autism Spectrum Disease who were educated in Northern Cyprus were included in the study. The universe of research included 48 autistic children in all private educational centers.  Food record method and healthy eating index were used to determine nutritional status. Nutrient inadequacy was determined by dietary reference intake. The growth parameters were evaluated by means of anthropometric measurements. Results: The study was completed with 40 children as 8 children refused to participate in the study. The 82.5% of children were male and 17.5% were female. The 45.0% of children with autism were also diagnosed with a different disease. According to the eating habits of children, 30% of autistic children were skipping meals and the most missed meal was breakfast. Consequently, 70% of the children were selective against some foods and the most omitted food group is vegetables. The most inadequate intake was calcium, iodine, vitamin D and fiber. In addition, 28.2% of the children have a poor diet quality and 47.5% were obese. Conclusions: It was determined that appropriate medical nutrition treatment and nutrition education were needed for children. There is also a need for further research.